THE ROLE OF MODERN TECHNOLOGIES IN TEACHING THE RUSSIAN LANGUAGE (Eureka Journal of Education & Learning Technologies, 2026)
This article explores the role of modern technologies in teaching the Russian language and their impact on learning effectiveness. It highlights the use of online platforms, mobile applications, virtual classrooms, and multimedia resources to develop learners’ speaking, listening, reading, and writing skills. The study also discusses how technology increases students’ motivation, supports individualized learning, and makes lessons more interactive. The article concludes that effective integration of digital tools can improve Russian language teaching when combined with appropriate teaching methods.
Keywords: Russian language, technologies, teaching methodology, online learning, digital platforms, interactive learning, multimedia.